DNA repair-related genes are the key for stony coral ancestors to survive under elevated levels of UVR - Wu, Tianzhen; Lei, Yanli; Jian, Zhimin (Frontiers in Marine Science, 2023)
DNA damage response (DDR) is a complicated network to defend against physical or chemical changes of DNA for all animals. Elevated levels of ultraviolet radiation (UVR) caused DNA damage, which was a reason for mass extinction that occurred at the Devonian/Carboniferous (D/C) boundary approximately 359 million years ago (Ma). However, the molecular adaptation of the stony coral ancestors, strangely survived the D/C boundary mass extinction, is not well understood. In the present study, the molecular clock analysis using fourfold degenerate sites of 1463 homologous genes of different stony coral species (a representative group of marine organisms with calcareous skeletons) suggested that their common ancestors originated 384.24 Ma, i.e., slightly earlier than the D/C transition. We identified 21 rapidly evolving genes (REGs) and 49 positive selection genes (PSGs) significantly enriched in diverse pathways, including the mitotic cell cycle process, intracellular protein transport, DNA synthesis involved in DNA repair. Interestingly, 4 REGs and 21 PSGs significantly enriched in DDR pathways, including the mitotic cell cycle process, DNA synthesis involved in DNA repair, and cellular response to DNA damage stimulus pathways. We hypothesize that enriched DDR genes are likely involved in the enhanced ability of ancient stony corals to detect and repair DNA damage. For example, POLE gene, which encodes the DNA polymerase epsilon catalytic subunit A, mediates interaction with the other three catalytic subunits by its nonenzymatic carboxy-terminal domain. POLE may potentially enhance the binding ability to other subunits to strengthen its function, because 8 positive selection sites were distributed in the C terminal of POLE and on the surface of the simulated 3D protein model. Therefore, our results, for the first time, demonstrated that the precise transfer of DNA information may help stony coral ancestors surviving in elevated levels of ultraviolet radiation, suggesting that DDR levels may be critical to the environmental adaptation of calcareous skeletal organisms during climate change.